PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENDORONG PEMAHAMAN PADA NILAI-NILAI PANCASILA DALAM PEMBELAJARAN PPKN PADA SISWA KELAS IV DI SDN 20 KAMPUNG LORONG TAHUN AJARAN 2023/2024 - Eva Andriani; Oskar Hutagaluh, Astaman (ADISAM PUBLISHER, 2024)
This study aims to describe and understand the process of implementing the CTL method to encourage understanding of Pancasila values in PPKn learning, to find out the inhibiting and supporting factors of the CTL method to encourage understanding of Pancasila values in PPKn learning, and to find out the evaluation of the application of the CTL method to encourage understanding of Pancasila values in PPKn learning. This study uses a qualitative approach and the type of research used is descriptive. The results of the study concluded that the process of implementing the CTL method to encourage understanding of Pancasila values involves several important aspects. Teachers relate the subject matter to students' daily experiences, encourage them to find their own problem solutions, and foster curiosity and the habit of asking questions. Learning also involves cooperation between students and the use of media or tools to make the learning process more effective. In addition, repetition of material is carried out to ensure understanding, and assessment is used to determine student achievement results. This method makes learning more contextual and meaningful. The inhibiting factors of the CTL method are as follows: lack of reading books and limited learning time. Supporting factors are as follows: professional teachers in teaching, adequate facilities and infrastructure, and students who are enthusiastic about learning. Evaluation of the application of the CTL method to encourage understanding of Pancasila values in PPKn learning can be concluded that the evaluation and assessment process is carried out systematically and continuously in education. In practice, the use of various evaluation methods, such as written tests, oral tests, and observations